Traffic problem in Kathmandu and Use of GIS in Urban Traffic Management - Marsani, Anil; Rajbamshi, Jeni (Journal on Geoinformatics, Nepal, 2004)
This paper first points out the root causes of traffic problem in the capital city of Nepal (Kathmandu) and hence some of the remedial measures to solve the problems are put forward along with the introduction of the concept of urban traffic management planning which is relatively new in the context of Nepal. At last this paper gives a comprehensive view to how GIS can be applied in the field of urban traffic management especially focusing on the travel demand analysis.